The Relationship Between Body Image Changes and Sexual Dysfunction in Breast Cancer Patients at Gorontalo Provincial Hospital - Nur Afdillah Husa; Ridha Hafid; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2025)
Breast cancer is a type of chronic non-communicable disease that grows in breast tissue. Breast cancer causes changes in the body that can cause negative body image problems that affect life on sexual function. The purpose of this study was to determine changes in body image with sexual dysfunction in breast cancer patients. This research method uses a correlation approach and Cross-Sectional design. The population in this study was obtained data at Prof. DR. Aloe Saboe Hospital in 2024 as many as 26 populations and at dr. Hasri Ainun Hospital as many as 23 populations, with Accidental Sampling techniques obtained a research sample of 44 respondents. The results showed that respondents with positive body image changes were 27 respondents (61.4%), negative body image changes were 17 respondents (38.6%) and respondents with good sexual function were 30 respondents (68.2%), and 14 respondents had poor sexual function (31.8%). The results of the chi square test obtained a significance value of p=value 0.017 (<0.05). In conclusion, there is a relationship between changes in body image and sexual dysfunction in breast cancer patients at the Gorontalo Provincial Hospital. The researcher's advice is aimed at the public, medical personnel and researchers to pay attention to the problems that arise in breast cancer.